Fostering Scientific Communication in Elementary Science Learning Through Game-Based Toulmin Argumentation - Putra, M. Jaya Adi; Mailinda, Desi Yusnita (FKIP Universitas Lampung, 2025)
This study aims to investigate the potential of science-themed educational games in improving the scientific communication skills of elementary school students. The main focus lies in examining the development of students' ability to express ideas, build arguments, and use scientific vocabulary in an authentic and engaging learning context. This study used a naturalistic qualitative approach with a case study design. Data were collected through participatory observation, audio-video recordings of classroom activities, and documentation of students’ work in grade V of a public elementary school. Thematic analysis was used to interpret the data, supported by the application of the Toulmin Argumentation Pattern (TAP) framework. This framework facilitates the identification of key argument components, including claims, data, guarantees, qualifications, and rebuttals. The findings show that the game